A multi‐theoretic perspective on trust and power in strategic supply chains - Ireland, R. Duane; Webb, Justin W. (Journal of Operations Management, 2007)
AbstractStrategic supply chains serve as a potential source of competitive advantage for firms. The ability of a strategy supply chain to engender cultural competitiveness, or joint entrepreneurship and learning aimed at filling market gaps, is a key path through which a strategic supply chain may become a competitive advantage. A balance of trust and power within the supply chain offsets uncertainty and risks associated with the behaviors underlying cultural competitiveness. Using a multi‐theoretic perspective, we discuss four strategies that firms use to balance a climate of trust and power in a strategic supply chain. Identifying an authority, generating a common supply chain identity, utilizing boundary spanning ties, and providing procedural and interactive justice are the strategies we discuss.